The Impact of Workload on Performance and Health of Air Traffic Controllers at JATSC Jakarta - Adrian Gagah Prakoso; Dhian Supardam; Martha Saulina (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the effect of workload on the performance and health of Air Traffic Controllers (ATCs) at the Jakarta Air Traffic Service Centre (JATSC). Using a descriptive quantitative approach with a cross-sectional design, data were collected from 41 controllers through validated instruments: NASA-TLX for workload, PSQI for sleep quality, and the Samn-Perelli Fatigue Scale for fatigue assessment. Results indicate a high workload (M=3.40) and compensatory effort patterns, where controllers exerted great effort (M=3.73) to maintain performance (M=3.80). All respondents experienced sleep disturbances, averaging 5.8 hours of sleep and poor sleep quality (mean PSQI=12.21). Night-shift fatigue increased by 68% compared to day shifts, with 51.2% reporting extreme fatigue. Health complaints were prevalent, including obesity (68.3%), headaches (85.4%), and musculoskeletal pain (75.6%). Fatigue strongly correlated with workload (rs=0.58, p<0.001) and sleep deprivation (rs=0.61, p<0.001). The study concludes that night shifts significantly affect physiological and psychological health, increasing operational safety risks due to extreme fatigue and microsleep. The findings highlight the need for fatigue risk management systems, optimized shift scheduling, and comprehensive wellness programs to enhance ATC health and performance.